Penggunaan Sistem Informasi Dalam Pengelolaan Data Olah Raga - Zuliarso, Eri; Sulastri, Sulastri; Diartono, Dwi Agus; Soelistijadi, R; Artati, Rara Sri (Intimas, 2024)
Komite Olahraga Nasional Indonesia (KONI) Kabupaten Kendal is an organization that is authorized and responsible for managing, fostering, developing and coordinating all sports activities in Kendal Regency. The Kendal Regency KONI management manages 54 sports with a total of 689 athletes, while there are 100 coaches. To manage this, an athlete information system is needed to manage data and information about athletes, including athlete profiles, match results, training schedules, health and fitness other information related to athletes. The primary function of an athlete information system is to assist coaches, team managers, and other support staff in making better decisions related to athlete development and team strategy. In addition, athlete information systems can also help improve athlete performance and overall team management efficiency. The Stikubank University lecturer team has built an Athlete and Coach Information System. This community service activity is carried out to provide training and assistance in the use of the Athlete Information System. The aim of this activity is to provide insight and skills in using Athlete Information Systems to administrators, athletes, and coaches so that the information systems built can help sports teams achieve better performance and gain greater competitive advantages.